Viden gennem kunstnerisk praksis. Om vidensbegrebet i kunstnerisk udviklingsvirksomhed - Haugland, Anne Gry (Passage - Tidsskrift for litteratur og kritik, 2018)
Anne Gry Haugland: “Knowledge through Artistic Practice. On the Concept of Knowledge in Artistic Research” Artistic research is by definition rooted in artistic practice and historically rooted in the artistic educational system. This article discusses the concept of artistic practice and the associated concept of knowledge using artistic research literature as well as examples from an artistic research project at The Royal Danish Academy of Music.